Proceedings of the 7th International Conference on Human-Agent Interaction 2019
DOI: 10.1145/3349537.3351894
|View full text |Cite
|
Sign up to set email alerts
|

Let Me Get To Know You Better

Abstract: With an ever increasing demand for personal service robots and artificial assistants, companies, start-ups and researchers aim to better understand what makes robot platforms more likable. Some argue that increasing a robot's humanlikeness leads to a higher acceptability. Others, however, find that extremely humanlike robots are perceived as uncanny and are consequently often rejected by users. When investigating people's perception of robots, the focus of the related work lies almost solely on the first impre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…by blending the humanlike and the mechanical face, keeping features from both of them. The particular set of facial textures utilized in this study is based on a interactive study we ran with the Furhat robot where we found that the morph robot elicited significantly higher discomfort than both the humanlike and the mechanical texture (Paetzel and Castellano, 2019). In previous work, we additionally validated the blending technique on another set of humanlike and mechanical textures and found some of the corresponding morphs to elicit significantly higher feelings of discomfort in participants compared to the original humanlike and mechanical textures (Paetzel et al, 2018).…”
Section: Robot Embodiment and Behaviormentioning
confidence: 95%
See 1 more Smart Citation
“…by blending the humanlike and the mechanical face, keeping features from both of them. The particular set of facial textures utilized in this study is based on a interactive study we ran with the Furhat robot where we found that the morph robot elicited significantly higher discomfort than both the humanlike and the mechanical texture (Paetzel and Castellano, 2019). In previous work, we additionally validated the blending technique on another set of humanlike and mechanical textures and found some of the corresponding morphs to elicit significantly higher feelings of discomfort in participants compared to the original humanlike and mechanical textures (Paetzel et al, 2018).…”
Section: Robot Embodiment and Behaviormentioning
confidence: 95%
“…(2) progressively exposing people to the multimodal behaviors of a robot improves people's perception of it (Paetzel and Castellano, 2019); and (3) the perceptual dimensions that contribute to people's mental image of the robot stabilize over time (Paetzel et al, 2020;Paetzel-Prüsmann et al, 2021). Hence, besides investigating the role of gaze patterns in a joint task with a focus on engagement, in this paper, we also focus on understanding how mutual gaze in a social chat develops over time within and between interaction sessions and how it relates to people's perception of the robotic interaction partner.…”
Section: Tracking Gaze Over Timementioning
confidence: 99%
“…Note that this appears to differ from studies in humanhuman interaction that indicate that first impressions are often maintained even after longer interactions. However, this effect may be reversed when it comes to social robots (Paetzel and Castellano, 2019;Paetzel et al, 2020). A related interpretation could be that the evaluation of individual components of a social robot, i.e., voice and appearance separately such as in the online survey, makes differences in these components stand out and trigger stereotypical perceptions, but when combined together with other elements in the interaction, the perception of these individual factors is overshadowed by the overall experience of the interaction and the ratings instead reflect their overall assessment of the interaction to different questionnaire questions.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that these hypotheses are formulated in order to formalise the study, rather than signalling expectations regarding the results, since previous work have indicated, e.g., that users' perception of an agent may change between first impression and a longer interaction (Paetzel and Castellano, 2019;Paetzel et al, 2020) and that subjects may-or may not-be more positive towards an agent that is portrayed as having their own nationality (see Section 3).…”
Section: Physical Robot Studymentioning
confidence: 99%
See 1 more Smart Citation